2017
DOI: 10.1093/mnras/stx2158
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy metallicity scaling relations in the EAGLE simulations

Abstract: Citation for published item:he ossiD w r¡ % imili nd fowerD i h rd qF nd pontD endree F nd h yeD toop nd heunsD om @PHIUA 9q l xy met lli ity s ling rel tions in the ieqvi simul tionsF9D wonthly noti es of the oy l estronomi l o ietyFD RUP @QAF ppF QQSREQQUUF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
137
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(170 citation statements)
references
References 130 publications
(256 reference statements)
31
137
0
2
Order By: Relevance
“…Using the semi-analytic model L-GALAXIES, combined with a state-of-the-art galactic chemical evolution model, Yates et al (2012) were able to reproduce the MZRgas of local star-forming galaxies but predicted a stellar metallicity significantly higher than the observation. De Rossi et al (2017) found similar results based on a high-resolution cosmological hydrodynamical simulation of EAGLE. Clearly, the challenge is to reproduce the relatively low average stellar metallicity at a given gas metallicity.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Using the semi-analytic model L-GALAXIES, combined with a state-of-the-art galactic chemical evolution model, Yates et al (2012) were able to reproduce the MZRgas of local star-forming galaxies but predicted a stellar metallicity significantly higher than the observation. De Rossi et al (2017) found similar results based on a high-resolution cosmological hydrodynamical simulation of EAGLE. Clearly, the challenge is to reproduce the relatively low average stellar metallicity at a given gas metallicity.…”
Section: Introductionsupporting
confidence: 67%
“…The trend of gas metallicity with stellar mass has been reproduced by semi-analytical galaxy evolution models (e.g., Calura et al 2009;Yates et al 2012) and hydrodynamical simulations (Guo et al 2016;De Rossi et al 2017). However, the MZRstar predicted by these models does not match the observed relation.…”
Section: Gas and Stellar Metallicity Comparisonmentioning
confidence: 93%
See 1 more Smart Citation
“…These simulations suggest that the stellar MZR evolves monotonically, with an increase in stellar metallicity of ∼0.3 dex at fixed stellar mass from z=1 to z=0. De Rossi et al (2017) presented stellar MZRs at four redshifts derived from a different suite of cosmological hydrodynamical simulations, the Evolution and Assembly of Galaxies and their Environments (EAGLE). The derived stellar MZRs came from a larger number of galaxies than those in Ma et al's (2016) study but with coarser spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The derived stellar MZRs came from a larger number of galaxies than those in Ma et al's (2016) study but with coarser spatial resolution. De Rossi et al (2017) predicted that the evolution of the stellar MZR is 0.2 dex from z=1 to z=0 at a stellar mass of 10 9.5 M e , slightly smaller than predicted by Ma et al (2016). The classical approach to measuring ages and metallicities of stellar populations is to use spectrophotometric indices such as Lick indices (Faber 1973;Worthey 1994), where the equivalent widths of some spectral features expected to correlate with metal abundance or age are measured and compared to model predictions.…”
Section: Introductionmentioning
confidence: 99%